STRATEGI MILLENIAL HUMAN CAPITAL DEVELOPMENTDALAM MENINGKATKAN KINERJA BISNIS - Tedi Setiawan, - (2023)
The study of banking performance raises various important issues, especially in the Millennial generation era. The performance of the banking industry, especially bank bjb, in 2023 will experience a decline, although there is good growth in terms of raising funds, lending and fee-based income. The research carried out applies a Strategic Management approach, especially in examining the influence of "millennial human capital development on business performance". The aim of the research carried out is to analyze the picture of "business performance" which includes the "external environment", "internal environment", "millennial human capital development", digital transformation implementation" and "work engagement programs" that influence each other. The research method uses quantitative methods with descriptive and verification research types. The research population that became the unit of analysis was 65 bank bjb branch offices, while the respondents were 65 branch managers using a saturated sampling technique. The research instrument used a questionnaire and data analysis techniques used "partial least square". Through research results, it is known that "business performance" is significantly influenced by "digital transformation implementation" and the "work engagement program". Furthermore, the "digital transformation implementation" and "work engagement program" are significantly influenced by "millennial human capital development" which is influenced by the "internal environment and external environment". Through the model in this research, it shows that "bank performance", both financial and non-financial, can be optimized with "organizational commitment", "value proposition" and "internal integration" through "millennial human capital" with integrity, competence, professionalism and competitiveness. The practical, implementable recommendations that can be carried out are integrating business strategy mapping and operational strategy formulation with the six variables studied in accordance with the bank bjb corporate plan and the Annual Directors' Strategic Direction (ADSD).